CORPORATE SOCIAL RESPONSIBILITY AND REAL EARNINGS MANAGEMENT: DOES BOARD GENDER DIVERSITY MATTER? - Boukattaya, Sonia; Halaoua, Sameh (International Journal of Accounting & Finance Review, 2022)
The purpose of this paper was to examine the moderating effect of board gender diversity on the relationship between corporate social responsibility (CSR) and real earnings management (REM). It drowns on French listed companies from 2005 to 2019. The results show that there is a positive relationship between CSR and REM. Our findings also show that this positive relation is moderated in firms with higher board gender diversity, mainly because female directors show a high socially responsible behaviour and are negatively associated with earnings management practices. Our results are robust to alternative board gender diversity measures, only after the quota law adoption. The positive relationship between CSR and REM suggests that companies with higher CSR performance are exposed to high discretionary behaviour. CSR can be strategically used by managers to hide unethical practices, such as real earnings management activities. In addition, the findings highlight the importance of board gender diversity in reducing agency costs and ensuring higher monitoring, particularly after the quota law adoption.JEL Classification Codes: G3, M14, M41.